Aplikasi Berbagai Koagulan Alami Serta Kajian Terhadap Kualitas Slab Yang Dihasilkan - Rusiardy, Iwan; Hendro, Marselus; Beni, Yulius (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2022)
Rubber processing in West Kalimantan is generally into lumps and slabs using formic acid as a coagulant. The high price of formic acid, not environmentally friendly and harmful to health, it opens up opportunities for the development of natural alternative coagulation. This study used natural coagulation ingredients in the form of lime fruit, noni fruit, and tamarind fruit. The content of organic acids in each of these fruits can reduce the pH of the latex to reach an isoelectric pH so that it can help the latex to clot. The purpose of this study was to determine the effect of natural agglomerates on the quality of the slab during storage. Rubber processing was carried out in the rubber plantation of Sungai Pelanduk Hamlet, Sanggau Regency and chemical analysis was carried out at the Chemical Laboratory of Plantation Product Management Study Program (PHP) Pontianak State Polytechnic PSDKU in Sanggau Regency. The results showed that the pH of the lime fruit extract, maram acid extract, fermented noni extract (respectively) was 1.8, 2.2 and 3.4. The higher the added concentration, the faster the latex coagulation process. The fastest clotting time was the addition of orange chili extract with concentrations of 20 and 30% (respectively) for 11 and 9 minutes. There was no significant effect as a result of the treatment on the volatile matter content and the resulting slab ash content. The PRI value of the slab ranges from 65.768% to 73.214%. The PRI value has met the quality requirements of SNI SIR 10 and SIR 20, namely at least 50% and 60%.